Thermodynamically equilibrium point defects in the low-dimensional systems - Mamalui, A.A.; Shelest, T.N.; Chashka, H.B. (Condensed Matter Physics, 1999)
The temperature dependencies of the electrical resistance of low-dimensional NbSe₃- and NbSe₂-single crystals were investigated in the range of 300–540 K. Measurements of resistance were produced along the chains for quasi-one-dimensional NbSe₃-single crystal and along the layer for quasi-two-dimensional NbSe₂-single crystal. On the temperature dependencies the exponential deviations from linear dependencies were observed. We suppose that such deviations of resistance are connected with the contribution of selenium equilibrium vacancies. Досліджено температурні залежності електричного опору низькорозмірних монокристалів NbSe₃ та NbSe₂ в температурному діапазоні 300–540 К. Вимірювання опору виконувалися вздовж ланцюжків для квазіодномірних монокристалів NbSe₃ та вздовж шарів для квазідвомірних монокристалів NbSe₂. На температурних залежностях опору виявлені експоненційні відхилення від лінійної залежності. Припускається, що ці відхилення пов’язані з внесками від рівноважних вакансій селену.